CONDIÇÕES DE MOBILIDADE URBANA E ACESSIBILIDADE - Fabíola de Oliveira Aguiar (Universidade Federal do Maranhão, 2012)
The present work aims to discuss about the mobility and accessibility conditions in São Luis / MA, comparing even though superficially São Paulo city in the 60's and São Luis at present. It is noteworthy the fact that Sao Luis still does not have mobility policies implemented, something that is being felt in everyday Iife by users who face more and more problems of urban circulation . The main avenues cannot stand anymore the burst of a growing number of vehicles.